A cogni-generative transit rail terminal using environmental design for enhanced wayfinding and commuter experience in Cubao - De Leon, Kaila Ann D.
In the field of architecture, legibility is crucial in facilitating smooth navigation for users within a transport terminal. However, excessive visual stimuli can cause confusion and disorientation, leading to visual pollution and hindering the wayfinding process. Previous research has identified that visual pollution is caused by proliferation of unorganized and distracting billboards and signages, which adversely affect individuals, often resulting in distraction and reduced focus in the indoor and outdoor environments. These effects can negatively impact visual attention and other cognitive processes. The role of cognitive processes -- such as attention, perception, comprehension, and decision-making -- concerning visual pollution and wayfinding has not been well-established. Despite this issue, there is a dearth of comprehensive studies that examine the architectural impact of visual pollution. This study aims to address this gap in knowledge by exploring the use of visual cognition in environmental design elements. The study will identify patterns and emerging themes based on grounded theory through participant mapping tasks, open-ended interviews, and site observations. The findings will be compared to existing literature to serve as a foundation for LRT-2 and MRT-3 stations. This study highlights the potential for visual cognition to aid in identifying potential architectural interventions in transport terminals, emphasizing wayfinding as a collaborative measure between environmental elements and environmental cues to support the decision-making process of passengers ultimately, the study bridges the gap between visual pollution and architectural design through visual cognition in enhancing wayfinding and commuter experience.